Public Engagement in the Implementation of the Policy on Waste Banking - Abdul Kadir Jaelani; Lusia Indrastuti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Kalisoro urban village is one of the tourist areas facing the issue of rising pile of garbage and the lack of knowledge of the waste. Especially in waste management this problem really needs more attention. Society involvement support is required in this waste management. Kalisoro Village waste management is an independent waste management village which involves the community. In this management, using the Reuse, Minimize, and Recycle 3R process. This study aims to explain the participation of independent waste village management by identifying the phases of participation society, the level of participation society and the factors affecting participation in the group. This study is presented in qualitative descriptive form, using in-depth interview technique in data collection and also using interactive data analysis technique for data triangulation. In this study, the culture represented by the Non-Governmental Organisations manages the consequence of involvement society in the management of the autonomous waste villages. Society ways of engagement are to contribute ideas, resources, funds, and engage in waste collection. But not all Kalisoro Village groups participated directly. In Kalisoro Village the level of participation society involves Citizen Power.Keywords: Participation; Society; Kalioso